In vivo identification of putative CPK5 substrates in Arabidopsis thaliana. (January 2022) - Yip Delormel, Tiffany; Avila-Ospina, Liliana; Davanture, Marlène; Zivy, Michel; Lang, Julien; Valentin, Nicolas; Rayapuram, Naganand; Hirt, Heribert; Colcombet, Jean; Boudsocq, Marie
Highlights: Transgenic lines expressing a constitutively active form of AtCPK5 induce cell death and target gene expression. Five new putative AtCPK5 substrates were identified by a phosphoproteomic approach. The 5 candidates were validated as direct targets of AtCPK5 by in vitro kinase assays. AtCPK5 interacted with the candidates in cytosol, membranes or nucleus. Abstract: Calcium signaling mediates most developmental processes and stress responses in plants. Among plant calcium sensors, the calcium-dependent protein kinases display a unique structure harboring both calcium sensing and kinase responding activities. AtCPK5 is an essential member of this family in Arabidopsis that regulates immunity and abiotic stress tolerance. To understand the underlying molecular mechanisms, we implemented a biochemical approach to identify in vivo substrates of AtCPK5. We generated transgenic lines expressing a constitutively active form of AtCPK5 under the control of a dexamethasone-inducible promoter. Lines expressing a kinase-dead version were used as a negative control. By comparing the phosphoproteome of the kinase-active and kinase-dead lines upon dexamethasone treatment, we identified 5 phosphopeptides whose abundance increased specifically in the kinase-active lines. Importantly, we showed that all 5 proteins were phosphorylated in vitro by AtCPK5 in a calcium-dependent manner, suggesting that they are direct targets of AtCPK5. We also detected several interaction patterns between the kinase and the candidates in the cytosol, membranes or nucleus, consistent with the ubiquitous localization of AtCPK5. Finally, we further validated the two phosphosites S245 and S280 targeted by AtCPK5 in the E3 ubiquitin ligase ATL31. Altogether, those results open new perspectives to decipher AtCPK5 biological functions.